New studies on Marandet (Central Niger) and its trade connections: an interim report - Magnavita, Sonja; Maga, Abdoulaye; Magnavita, Carlos; Idé, Oumarou A. (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
In early 2007, preliminary archaeological investigations were carried out at Marandet, central Niger. They aimed at understanding the history of the settlement, its economic role in an early trans-Saharan trade and relation to the historical Maranda. An interim report on the first archaeological season is presented. It provides a general description of the site, the material culture of its inhabitants and their external contacts.The article will be available as a PDF in the near future.